2009
DOI: 10.1097/ana.0b013e3181a71f11
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of the Association of Anesthesia and Hernia Repair Surgery With Behavioral and Developmental Disorders in Young Children

Abstract: Recent animal studies have shown that commonly used anesthetic agents may have serious neurotoxic effects on the developing brain. The purpose of this study was to assess the association between surgery for hernia repair and the risk of behavioral and developmental disorders in young children. We performed a retrospective cohort analysis of children who were enrollees of the New York State Medicaid program. Our analysis involved following a birth cohort of 383 children who underwent inguinal hernia repair duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
329
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 453 publications
(349 citation statements)
references
References 17 publications
10
329
3
7
Order By: Relevance
“…48 DiMaggio et al, using a New York State Medicaid database, showed that children younger than 3 years who were given general anesthesia for inguinal hernia repair had a greater than twofold risk of developmental or behavioral disorders than did agematched control children. 49 A potential bias of this study is that children undergoing surgery at a young age may also be predisposed to learning or cognitive disorders. Bartels et al attempted to address this issue by using the Netherlands Twin Registry to evaluate monozygotic concordant-discordant twins.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 94%
“…48 DiMaggio et al, using a New York State Medicaid database, showed that children younger than 3 years who were given general anesthesia for inguinal hernia repair had a greater than twofold risk of developmental or behavioral disorders than did agematched control children. 49 A potential bias of this study is that children undergoing surgery at a young age may also be predisposed to learning or cognitive disorders. Bartels et al attempted to address this issue by using the Netherlands Twin Registry to evaluate monozygotic concordant-discordant twins.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 94%
“…However, variations in these human study approaches such as different assessment tools have led to inconsistent conclusions; some groups reported cognitive impairment (DiMaggio et al. 2009, 2011; Sprung et al. 2009; Wilder et al.…”
Section: Introductionmentioning
confidence: 99%
“…12 Findings from clinical studies are mixed, with some studies showing a twofold increase in cognitive disability in children with anesthetic exposure, whereas others show no association. [13][14][15][16][17][18][19][20] In studies demonstrating an association of anesthesia with disability, only children with multiple anesthetic exposures have been associated with deficits, but an effect with a single exposure has not been identified. 14,18,20 These clinical studies have used International Classification of Diseases, 9th Revision diagnosis codes, standardized tests, and evaluations by parents and teachers as outcome measures, but none to date has used a battery of multiple directly assessed neuropsychological outcome measures.…”
mentioning
confidence: 99%